First record of Diapoma pyrrhopteryx Menezes and Weitzman, 2011 (Characiformes: Characidae) from freshwaters of Argentina - Almirón, Adriana Edith (2016)
Fil: Almirón, Adriana Edith. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Vertebrados; Argentina